Kebutuhan Belajar Masyarakat Adat dalam Kebijakan Pendidikan - Sania Nur Maulida; Nabila Syifa Khoirunnisa; Sopi Novitasari; Eneng Siti Rohamah; Ira Sri Damayanti (University of Nahdlatul Ulama Pasuruan, 2021)
The purpose of this study is to determine how the learning needs of indigenous peopples in education policy. The research menthod used is literature (library) in the form of books, notes and previous research reports, and also this study uses the SWOT (Strenghts, Weaknesses, Oppotunities dan Threats). In accordance with the law. The problem in the policy is how the educational needs of indigenous peopples can be met such as access to education, facilities an infrastucture as wellas beliefs or characteristics of these indigenous peopple. For this reason, so that learning activities continue and the need for learning is carried out, the learning procces will be adapted to indigenous people.